2018
DOI: 10.1002/app.46696
|View full text |Cite
|
Sign up to set email alerts
|

Thermoviscosifying polymers based on polyether prepared from inverse emulsion polymerization

Abstract: Thermoviscosifying polymers are attractive for enhancing oil recovery owing to their exceptional thickening power as temperature increases. However, the polymers reported to date show inadequacies including obligatory high polymer concentration to get the thermothickening ability because of their low molecular weight (MW), and inconvenient post-treatment due to the high viscosity after manufacturing. To overcome these drawbacks, inverse emulsion polymerization was used here for preparing polyether-based thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In addition to ionic strength, high temperatures of the reservoirs decrease the viscosity reached by the polymer in the aqueous medium . Thus, it would be interesting to develop HPAM derivatives with the ability to increase viscosity under the severe conditions of the reservoir, such as high temperature and high ionic strength …”
Section: Introductionmentioning
confidence: 99%
“…In addition to ionic strength, high temperatures of the reservoirs decrease the viscosity reached by the polymer in the aqueous medium . Thus, it would be interesting to develop HPAM derivatives with the ability to increase viscosity under the severe conditions of the reservoir, such as high temperature and high ionic strength …”
Section: Introductionmentioning
confidence: 99%
“…A latest core flooding test with equal initial viscosity of TVP and conventional polymer solutions in our laboratory [51] also demonstrated that TVP polymer can increase 2.1 % more oil recovery factor than solution and its counterpart at 45 8C.…”
Section: Enhanced Oil Recoverymentioning
confidence: 68%
“…Very recently, our team pushed the MW of such graft polymers to 7.8 10 6 g · mol À1 with inverse polymerization, thus at just 0.2 wt% polymer concentration, the graft polymers exhibit profound thermothickening behavior. [51] In addition, the dissolution time of such polymers can be shortened from more than 2 hours on powder product to less than 10 minutes for the emulsion counterpart.…”
Section: Tvps Containing Peo-ppo-peo Side Chainsmentioning
confidence: 99%
“…Those characteristics allow for great potential applications in fields like food science [4], damping [7], tissue engineering [8], and oil development [9,10]. Over the past few decades, smart viscoelastic fluids that respond reversibly to environmental stimuli, e.g., temperature [11][12][13][14][15], pH [16,17], light [18], and CO 2 [19], to demonstrate tunable rheological properties have drawn extensive attention both from engineers in industry and fundamental theoretical scientists. Among above triggers, CO 2 has garnered considerable interests recently due to its nontoxicity, low cost, high availability, and good biocompatibility [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%